POLA INTERVENSI STAKEHOLDER DALAM PENGELOLAAN PESISIR TRIMUL YO KECAMA T AN GENUK KO T A SEMARANG - Reny Yesiana; Muhammad Hedy Zuliana; Saly Diah Ayu Kirana (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2017)
The kinds of aid and intervention who already implemented as an effort to protect coastal areas in Semarang City. Not only from government, but from the private and academics also have helped on coastal areas management. These aid not only embodied physically likes the giving of mangrove seedlings, build up the breakwater, but also the soft skills development likes training to manage fishery and marine to make something useful. These intervention was held for two objectives, the first is to protect coastal areas and the last is to empower the communities on there. These intervention be expected to make a change the quality of life in coastal areas better. The aim of this research is to assest the scheme of stakeholder’s intervention on coastal areas in Trimulyo, Semarang City. Sampling technique that used in this research snowballing sampling, because the stakeholder information who involved will be asked before to the communities on there. After that, the interview will be continue to the governement, private, academics and the scheme each stakeholder will be seen. Based of the result, coastal areas management who already implemented by the government, it was created 4 schemes, they are: the government non collaboration or independently give the intervention and the aid directly to communities, every government agencies do the collaboration with the other government agencies, multistakeholder collaboration, they are NGO, Government, academics and Privat sectors through CSR programs. Each scheme has the weaknesses and strengths, the collaboration basically emphasized, because a lot of people can give the input and controlling the intervension implementation.The intervension who implemented has the positive impact for environment and society, they are: the decrease of environtmental degradation, reduction the threat of cataclysm, climate change on coastal areas related the rehabilitation, rejuvenation environmental ecosystem. In other side, there are too many activities about training to the society makes them more resilience on their economy activties.